2016
DOI: 10.1098/rsob.160225
|View full text |Cite
|
Sign up to set email alerts
|

A role for the p53 tumour suppressor in regulating the balance between homologous recombination and non-homologous end joining

Abstract: Loss of p53, a transcription factor activated by cellular stress, is a frequent event in cancer. The role of p53 in tumour suppression is largely attributed to cell fate decisions. Here, we provide evidence supporting a novel role for p53 in the regulation of DNA double-strand break (DSB) repair pathway choice. 53BP1, another tumour suppressor, was initially identified as p53 Binding Protein 1, and has been shown to inhibit DNA end resection, thereby stimulating non-homologous end joining (NHEJ). Yet another t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 63 publications
0
35
0
Order By: Relevance
“…In the absence of p53, 53BP1 foci formation at damage sites following ionizing radiation is impaired. Instead, there is an increase in BRCA1 recruitment, and these changes are independent of the degree of damage or cell cycle stage [72]. Such a transcription-independent role for p53 in defining the choice of repair pathway has significant implications for tumorigenesis and tumor response to chemotherapy.…”
Section: Pathway Choice: Hr or Non-homologous End Joining (Nhej)mentioning
confidence: 99%
“…In the absence of p53, 53BP1 foci formation at damage sites following ionizing radiation is impaired. Instead, there is an increase in BRCA1 recruitment, and these changes are independent of the degree of damage or cell cycle stage [72]. Such a transcription-independent role for p53 in defining the choice of repair pathway has significant implications for tumorigenesis and tumor response to chemotherapy.…”
Section: Pathway Choice: Hr or Non-homologous End Joining (Nhej)mentioning
confidence: 99%
“…γH2AX is phosphorylated at serine 139 by ATM kinase upon the generation of a DSB. As a DSB marker, DSB damage can be analyzed by quantifying γH2AX foci, size, and quality (Lorat et al, 2016;Moureau et al, 2016 demonstrated that p53 binding protein 1 (53BP1) foci contain DSB sites (Schultz et al, 2000). XRCC1, a necessary factor for singlestrand break repair; Ku70, which plays a role in nonhomologous end joining (NHEJ); and Rad51, which functions in homologous recombination repair, are also known to participate in DNA damage repair (Schultz et al, 2000;Lord & Ashworth, 2012;Moureau et al, 2016;Whitehouse et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…p53 has been implicated in transcriptionally-independent regulation of different DNA repair 10 pathways like nucleotide-excision repair, base-excision repair and mismatch repair(3). P53 is also emerging as an important factor in regulating the balance between homologous repair (HR) and non-homologous end-joining repair (NHEJ) (4,5). Since choice of repair is strongly tied to damage sensing, these findings indicate that there may be an unreported role for p53 at the crossroads of initial damage sensing and downstream recruitment of and/or transcriptional 15 regulation of relevant repair factors.…”
Section: Main Textmentioning
confidence: 99%